Chromosomal structures and repetitive sequences divergence in Cucumis species revealed by comparative cytogenetic mapping - Zhang, Yunxia (BMC Genomics, 2015)
BACKGROUND: Differentiation and copy number of repetitive sequences affect directly chromosome structure which contributes to reproductive isolation and speciation. Comparative cytogenetic mapping has been verified an efficient tool to elucidate the differentiation and distribution of repetitive sequences in genome. In present study, the distinct chromosomal structures of five Cucumis species were revealed through genomic in situ hybridization (GISH) technique and comparative cytogenetic mapping of major satellite repeats. RESULTS: Chromosome structures of five Cucumis species were investigated using GISH and comparative mapping of specific satellites. Southern hybridization was employed to study the proliferation of satellites, whose structural characteristics were helpful for analyzing chromosome evolution. Preferential distribution of repetitive DNAs at the subtelomeric regions was found in C. sativus, C hystrix and C. metuliferus, while majority was positioned at the pericentromeric heterochromatin regions in C. melo and C. anguria. Further, comparative GISH (cGISH) through using genomic DNA of other species as probes revealed high homology of repeats between C. sativus and C. hystrix. Specific satellites including 45S rDNA, Type I/II, Type III, Type IV, CentM and telomeric repeat were then comparatively mapped in these species. Type I/II and Type IV produced bright signals at the subtelomeric regions of C. sativus and C. hystrix simultaneously, which might explain the significance of their amplification in the divergence of Cucumis subgenus from the ancient ancestor. Unique positioning of Type III and CentM only at the centromeric domains of C. sativus and C. melo, respectively, combining with unique southern bands, revealed rapid evolutionary patterns of centromeric DNA in Cucumis. Obvious interstitial telomeric repeats were observed in chromosomes 1 and 2 of C. sativus, which might provide evidence of the fusion hypothesis of chromosome evolution from x = 12 to x = 7 in Cucumis species. Besides, the significant correlation was found between gene density along chromosome and GISH band intensity in C. sativus and C. melo. CONCLUSIONS: In summary, comparative cytogenetic mapping of major satellites and GISH revealed the distinct differentiation of chromosome structure during species formation. The evolution of repetitive sequences was the main force for the divergence of Cucumis species from common ancestor. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-015-1877-6) contains supplementary material, which is available to authorized users.